Correction: Synthesis of DNA-guided silver nanoparticles on a graphene oxide surface: enhancing the antibacterial effect and the wound healing activity. Issue 67 (29th November 2019) - Tong, Chunyi; Zou, Wei; Ning, Weimin; Fan, Jialong; Li, Li; Liu, Bin; Liu, Xuanming
Abstract : Correction for 'Synthesis of DNA-guided silver nanoparticles on a graphene oxide surface: enhancing the antibacterial effect and the wound healing activity' by Chunyi Tong et al., RSC Adv., 2018, 8, 28238–28248.